Práticas de leitura e o gênero canção rap na perspectiva do interacionismo sociodiscursivo: uma proposta didática para o ensino - Pinheiro, Naiara Fernandes (2023)
The teaching of reading, despite still being a recurrent subject in the school environment, often becomes a boring activity, since it is performed as a linear process, word by word, with the aim of extracting some meaning from the text. Because it is a genre that evokes several feelings and provides a pleasing experience, some reading activities (with songs from another genre) were carried out in Portuguese Language classes, at the nineth grade classes of junior high school in the final years. The present theoretical work of propositional nature and qualitative basis, focusing on teaching of reading from the rap song genre, has as objective to propose activities for the improvement of reading skills from rap songs in students of the ninth grade of junior high school in the final years. The choice for this musical genre came up, firstly, from a great appreciation of the song genre as it is a genre that is very present in Brazilian people’s daily lives, so, when using it, in addition of presenting a little of our culture and using a genre that is present in the students’ daily lives, it evokes a new look for a reflection on social problems and the values present in the songs, which are present in our society. Thus, when working with this genre, it will be considered the student’s linguistic repertoire. This teaching practice is relevant once it addresses linguistic studies integrated with cultural elements, considering the students’ world knowledge and the social context in which they are inserted. With the participation of the students, teaching and learning opportunities are expanded, leading to a reflection on what is addressed in the lyrics of the rap music genre. The research will be based on the theoretical assumptions of Socio-discursive Interactionism (SDI) outlined by Broncarkt (2012), who defends language teaching within a social context in which interaction occurs. And theorists of reading such as Kleiman (2016) and Leurquin (2001) who emphasize the importance of this teaching in the construction of critical and participatory readers. For this, the choice for song and rap, in the classroom, was propitious in order to provide the students the contact with material that enables their effective participation, inciting the debate and ensuring the construction of a critical sense of each student.